Second nationwide surveillance of bacterial pathogens in patients with acute uncomplicated cystitis conducted by Japanese Surveillance Committee from 2015 to 2016: antimicrobial susceptibility of Escherichia coli, Klebsiella pneumoniae, and Staphylococcus saprophyticus. Issue 6 (June 2019) - Hayami, Hiroshi; Takahashi, Satoshi; Ishikawa, Kiyohito; Yasuda, Mitsuru; Yamamoto, Shingo; Wada, Koichiro; Kobayashi, Kanao; Hamasuna, Ryoichi; Minamitani, Shinichi; Matsumoto, Tetsuya; Kiyota, Hiroshi; Tateda, Kazuhiro; et al.
Abstract: The Japanese Surveillance Committee conducted a second nationwide surveillance of antimicrobial susceptibility patterns of uropathogens responsible for acute uncomplicated cystitis (AUC) in premenopausal patients aged 16–40 years old at 31 hospitals throughout Japan from March 2015 to February 2016. In this study, the susceptibility of causative bacteria ( Escherichia coli, Klebsiella pneumoniae, Staphylococcus saprophyticus ) for various antimicrobial agents was investigated by isolation and culturing of organisms obtained from urine samples. In total, 324 strains were isolated from 361 patients, including E. coli (n = 220, 67.9%), S. saprophyticus (n = 36, 11.1%), and K. pneumoniae (n = 7, 2.2%). The minimum inhibitory concentrations (MICs) of 20 antibacterial agents for these strains were determined according to the Clinical and Laboratory Standards Institute (CLSI) manual. At least 93% of the E. coli isolates showed susceptibility to fluoroquinolones and cephalosporins, whereas 100% of the S. saprophyticus isolates showed susceptibility to fluoroquinolones and aminoglycosides. The proportions of fluoroquinolone-resistant and extended-spectrum β-lactamase (ESBL)-producing E. coli strains were 6.4% (13/220) and 4.1% (9/220), respectively. The antimicrobial susceptibility of K. pneumoniae was retained during the surveillance period, while no multidrug-resistant strains were identified. In summary, antimicrobial susceptibility results of our second nationwide surveillance did not differ significantly from those of the first surveillance. Especially the numbers of fluoroquinolone-resistant and ESBL-producing E. coli strains were not increased in premenopausal patients with AUC in Japan.